About the International Scientific and Practical Conference in Bishkek - Tytarenko, Vita Volodymyrivna (Relihijna svoboda, 2020)
About the Work of the International Scientific-Practical Conference "Secularism, Secularism, Religion in the Post-Soviet Space: Historical, Legal and Philosophical-World Aspects" was held in Bishkek, Kyrgyzstan, October 23-25, 2019.